Country Partnership Framework for the Republic of Mali the Period FY16-19 - World Bank Group (World Bank, Washington, DC, 2016)
Prior to the political and security crisis of 2012, Mali, a large landlocked country in West Africa already ranked among the poorest countries in the world. In early 2012, the vast northern regions fell under the control of extremist forces, while a coup d’état in Bamako threw the country into political instability and turmoil. A strong international military response in early 2013 prevented further destabilization, though part of the North remains outside government control and insecurity has spread to Bamako and the South. The signing of a peace agreement in June 2015 has revived hopes for peace and stability. The WBG has continued to support Mali throughout the crisis. An Interim Strategy Note (ISN, FY14-15) addressed the root causes of Mali’s underestimated fragility, namely weak governance, extremely high demographic growth and the consequences of climate change. This CPF will continue to address the drivers of Mali’s fragility, with a strong focus on governance, while building on the progress and experience of the ISN. Drawing from the recent Systematic Country Diagnostic (SCD), which stresses the criticality of improving rural livelihoods to sustainable poverty reduction, the Framework intends to contribute to improving rural incomes by increasing productivity and resilience in the four livelihood zones of the country. Accordingly, the CPF proposes orientations for the WBG engagement around three areas of focus: (i) improve governance, by strengthening public resource management at central and local levels and fostering citizen engagement; (ii) create economic opportunities, by enhancing the productive capacity of smallholders, increasing agricultural value added and diversification to catalyze transformation, and improving basic services by developing infrastructure and connectivity; and (iii) build resilience, by developing human capital, strengthening safety nets, improving risk management mechanisms for the poor and vulnerable and mitigating climate shock. A comprehensive program has been proposed for the first two years of the CPF that includes knowledge activities and development policy operations to address the binding constraints to poverty reduction, as well as citizen engagement, investment financing, partner-funded and joint IFC/IDA investments and guarantees. Key areas include the reinsertion of ex-combatants, competitiveness and agricultural productivity, statistical capacity, climate change, water and sanitation, safety nets programs, energy, irrigation and transport.